INVENTARISASI DAN PEMANFAATAN TUMBUHAN OBAT TRADISIONAL DI KEBUN DENASSA, GOWA, SULAWESI SELATAN - Rohmawati, Yuni; ENDARTIWI, SRI SULARSIH (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2025)
Denassa Garden, Gowa, South Sulawesi, is a conservation area with great potential in preserving medicinal plants and becoming a means of public education. However, until now, there has been no systematic inventory related to the types and uses of medicinal plants in this area, so there is a risk of losing traditional knowledge. This study aims to inventory the types of traditional medicinal plants and analyze how they are used. Qualitative research method with a case study method research design. The results of the study stated that there are 23 types of traditional medicinal plants that are used for the treatment of various diseases, including internal organ diseases, reproduction, external organs or skin diseases, respiratory tract, digestive tract, joints and bones as well as for health care. The most widely used plant part is leaves (65%), with the main processing method in the form of boiling (71%). In addition, medicinal plants in Denassa Gardens are also used for beauty, education, and biodiversity conservation purposes. The inventory of medicinal plants in Denassa Gardens shows the importance of documentation and preservation of traditional medicinal plants to support public health and maintain the sustainability of biological resources. Keywords : Inventory, Traditional Medicinal Plants, Utilization, Denassa Garden